Autonomous navigation in mobile telepresence robots using a kinect sensor and robot operating system - Bhujel, Niraj; Teerapat Sanguankotchakorn; Attaphongse Taparugssanagorn; Nakamura, Shinichi; Asian Development Bank-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
Autonomous navigation in telepresence robots is a promising technology to enhance communication experience by reducing mental effort of operating robot in remote environment. One of the major challenges in implementing autonomous navigation is huge cost of sensors and reliability of such system. In this research work, autonomous navigation is implemented in TurtleBot using open-source Robot Operating System (ROS) and Kinect sensor. The reliability and accuracy of the implemented autonomous navigation is measured using Benchmark for Robot Indoor Navigation (BRIN) framework. Finally, an architecture is proposed to implement autonomous navigation using smart devices like Google Tango Project that is equipped with gyro-meter, accelerometer and depth sensor making it perfectly suitable for indoor localization.
A research submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Information and Communication Technologies, School of Engineering and Technology
Research Studies Project Report (M. Eng.) - Asian Institute of Technology, 2016
Keywords: Autonomous robots -- Computer programs; Kinect (Programmable controller); Mobile robots